Design of the KIMIMIX Learning Management System as a future practicum innovation - Muhamad Firmansya Junus; Asna Istikmalatul Muktamaroh; Henry Praherdhiono; Yerry Soepriyanto (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Innovation in chemistry laboratories can be integrated with the help of a Learning Management System (LMS). This innovation allows educators to provide video content, modules, and auxiliary tools to enhance students' performance in conducting experiments in the laboratory. This research aims to develop a Moodle-based KIMIMIX Learning Management System Design that adapts the Outcome Based Education (OBE) theory, developed by the skills needed by chemistry students who will be oriented toward future practical innovation. This research and development method adapts the ADDIE model at the Analysis and Design stage. The research sample comprised 24 students taking the first semester of the Chemistry study program at Gorontalo State University. The research process is a preliminary study, needs analysis, material analysis, media analysis, and media innovation analysis with data collection techniques using an open-ended questionnaire given to 114 students. The results of the design stage include media specifications (media formats, text fronts, grammar, themes, supporting software), flowcharts, and design implementation. The KIMIMIX LMS research design as a future practicum innovation is declared ready to implement the design at the product development stage. The detailed design is hoped to produce a sophisticated LMS product for chemical practicums. AbstrakInovasi dalam praktikum kimia dapat diintegrasikan dengan bantuan Learning Management System (LMS), inovasi ini memungkinkan pendidik menyediakan konten video, modul dan tools pembantu untuk meningkatkan performa praktikan dalam melakukan eksperimen di laboratorium. Penelitian ini bertujuan untuk mengembangkan Desain Learning Management System KIMIMIX berbasis Moodle yang mengadaptasi teori Outcome-Based Education (OBE) yang dikembangkan sesuai dengan keterampilan/skill yang dibutuhkan mahasiswa kimia yang akan berorientasi pada inovasi praktikum masa depan. Metode penelitian dan pengembangan ini mengadaptasikan model ADDIE pada tahap Analisis dan Desain. Sampel penelitian ini yaitu 24 mahasiswa Program studi Kimia Universitas Negeri Gorontalo yang sedang menempuh semester satu. Tahapan penelitian ini yaitu studi pendahuluan, analisis kebutuhan, analisis materi, analisis media, dan analisis inovasi media dengan teknik pengumpulan data menggunakan jenis angket terbuka yang diberikan kepada 114 mahasiswa. Hasil tahapan design meliputi spesifikasi media (format media, font teks, tata bahasa, tema, software pendukung), flowchart, dan implementasi desain. Desain penelitian LMS Kimimix sebagai inovasi praktikum masa depan dinyatakan telah siap untuk mengimplementasikan desain pada tahap pengembangan produk. Desain yang telah terancang dengan detail diharapkan dapat menghasilkan sebuah produk LMS yang mutakhir untuk pelaksanaan praktikum kimia.Kata Kunci: inovasi praktikum; KIMIMIX; learning management system; moodle; outcome based education